solve :(2 + i)x^{2 }- (5 -i)x + 2(1-i) = 0

(2 + i )x^{2} - ( 5 - i )x + 2 ( 1 -i) = 0

=> 2x^{2} + ix^{2} - 5x +ix + 2 - 2i =0

=> 2x^{2} -5x +2 = -ix^{2 }- ix +2i

=>( x-4 )( x-1) = -i (x2 + x -2)

=>(x-4)(x-1) = -i (x+2)(x-1)

=> (x-4)/ (x+2) = -i

sq both sides we get ;;........

(x-4)^{2} / (x+2)^{2} = i^{2}

(x-4)^{2} = - (x+2)^{2 }

x^{2 }+ 16 - 8x = -x^{2 }- 4 - 4x

2x^{2} +20 -4x =0

x^{2} - 4x +10=0

sovle it furthur by quadratic formula...........

**thumps ^{ up} plzz................**

**
**